Pengaruh Kompetensi Digital dan Dukungan Teknologi terhadap Kinerja Karyawan pada Pabrik Kacang Kedelai Cukup Berkah di Kabupaten Bandung - Syam Adi Pangestu; Umban Adi Jaya (Jurnal Manajemen Dirgantara, 2026)
The development of the industrial era 4.0 requires companies to be able to adapt through effective human resource management to improve competitive-ness and organizational performance. One important factor in improving em-ployee performance is digital competence and adequate technological support. This study aims to analyze the influence of digital competence and technologi-cal support on employee performance (at the Cukup Berkah soybean factory in Bandung Regency). The research approach is quantitative with an associative research design. Data analysis uses multiple linear regression analysis to determine the effect of each independent variable on the dependent variable. The data collection technique uses a questionnaire that has been tested for validity and reliability. The sample in this study amounted to 30 employees. The sampling technique was purposive sampling. The results of the study show that digital competence does not have a significant effect on employee performance partially. The t-test results show a significance value of 0.096 (> 0.05), technological support also does not have a significant effect on employee performance partially. Based on the t-test, the significance value is 0.705 (> 0.05).